Press Release in Media Policy in the Context of European Legislation on Transparency of Advertising - Vaišnys, Andrius (Information & Media, 2026)
The purpose of this article is to explore the discourse of power in the media system, which has become an issue of information policy, determined by the penetration of public relations into the structure of content created by participants in the media system, as well as agreements between the legislator and media owners. The article analyzes the formation of the corporate media model by examining information policy decisions that create contradictory conditions for journalism in Lithuania. By using systems theory, as well as communication and information theories, the author of the article reveals how the discourse of power is constructed in recent Lithuanian media policy. This article, based on the principles of gatekeeper theory, analyzes the relationship between the media system participants, i.e., between legislators and media owners. Since Lithuanian media outlets have been able to publish press releases in full since 2024, and their content is not assessed for advertising, journalists’ publications are presented in a structured context of non-critical content.The author examines the case of amendments to the Public Information Law, when the Parliament of the Republic of Lithuania included a definition of a media release (‘press release’) in this law. This amendment allows a media owner to decide whether a press release prepared by a public relations professional from a company or organization is an advertisement; in addition, the owner can publish it in its entirety free of charge as part of prepared news reports. Although the Directive 2010/13/EU of the European Parliament and of the Council of 10 March 2010 on the coordination of certain provisions laid down by law, regulation or administrative action in Member States concerning the provision of audiovisual media services defines the criteria for audiovisual commercial communication (and surreptitious audiovisual commercial communication), advertising and hidden advertising, as well as the definition of sponsorship, the Lithuanian legislator creates an autonomous norm in the national legal act with the new amendment.
Keywords: European Union regulations; legislator; media gatekeeper theory; media policy; power discourse; public relations; systems theory